Etika bisnis dalam kajian hukum al-qur’an dan hadist - Suryadhani, Resna Ayu (Maliki Interdisciplinary Journal, 2024)
Business is an activity in running a business carried out by individuals or a series of groups by striving to buy goods and services in order to get profit or profit. A business established has several objectives, namely to achieve a level of welfare for business owners and the surrounding community, create jobs, meet consumer needs by selling goods and / or services, maintain business existence in the long term. Business in Islam is all activities that aim to get profits that are carried out based on sharia and Islamic values. Business in Islam aims to obtain optimal profits and get pleasure from Allah SWT so that the company can grow and float in the blessings of Allah SWT. In the Qur'an it has been affirmed that man is encouraged to do business in search of some of the sustenance provided by Allah to meet the needs and necessities of life. Islam has also taught how to do business well without harming yourself and others. So that it can provide mutual benefits for fellow human beings. In today's millennial era, business is very well conceptualized and creative, so many people compete with each other and compete to increase the prestige and existence of their business, so often fraud is used as a shortcut to accelerate the improvement of the development of a business.declining morale in doing business will cause business losses both to business owners, business partners and consumers. Many people have forgotten the value of values that have been taught by Islam in doing business so that it causes a lot of losses to dzolim to fellow human beings.